The Impacts of Body Sculpting Exercise and Age on Body Fat and Waist Circumference - Nataloka, Sukesi Widya; Sulaiman, Sulaiman; Rahayu, Setya (Journal of Physical Education and Sports, 2019)
Large waist circumference and excessive body fat, more than that normal size, is a red flag that has contributed negatively for the human body. This study aims at recognizing and analyzing: the difference between the impacts of Zumba toning and piloxing SSP exercise on body fat, the difference between the impacts of Zumba toning and piloxing SSP exercise on waist circumference, the difference between the impacts of early and late adulthood on body fat, the difference between the impacts of early and late adulthood on waist circumference, the interaction between the types of body sculpting workout and age on body fat, the interaction between the types of body sculpting workout and age on waist circumference. Experiment method with 2x2 factorial design was used as the method of this study. The data were analyzed using the Analysis of Varian (ANOVA) on the significance level ÃŽÂ± = 0.05. The independent variable is Zumba toning and piloxing SSP. An early and late adulthood become the attribute variable, while body fat and waist circumference become the dependent variable. The result of this study is there is no difference in impact between Zumba toning and piloxing SSP exercise on body fat with the significance value is 0.977 > 0.05, there is a difference in impact between Zumba toning and piloxing SSP exercise on waist circumference with the significance value is 0.028 < 0.05, there is a difference in impact between early and late adulthood on body fat, with the significance value 0.034 < 0.05, there is no difference in impact between early and late adulthood on waist circumference, with the significance value, is 0.360 > 0.05, there is an interaction between the types of body sculpting workout and age on body fat, with the significance value is 0.561 > 0.05, (6) there is an interaction between the types of body sculpting workout and age on waist circumference, with the significance value is 0.001 < 0.05.